English in Southeast Asia and ASEAN : transformation of language habitats - Azirah Hashim; Leitner, Gerhard, 1944- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"English in Southeast Asia and ASEAN embeds English in its various regional Southeast Asian and political ASEAN language habitats. Addressing the history, developmental stages and contacts with other languages, it provides in-depth information on the region and its political organisation. In doing so, it analyses the geo-political division of the region between former Anglophone and non-Anglophone colonies and shows that this distinction has led to considerable differences in the status and texture of English. This analysis includes the role and impact of American English in mainland and maritime Southeast Asia to highlight the linguistic properties of English and its linguistic and socio-political development, English used in specific domains, language policies and concludes with the future of English and future challenges. This book therefore provides an integrative survey of the various roles of English in ASEAN member states and studies the transformation of entire language habitats, including the major national and regional languages that participate in this process. It also explains how new societies emerge with their conflicting identities and their aspirations to act regionally or even globally. A valuable resource for scholars and students in the fields of world Englishes, Asian studies and those interested in language contact, policy and planning"--
English and local languages in Southeast Asia and ASEAN -- The transformation of local language habitats -- History of English in Southeast Asia -- Texture and features of English -- Language contact and the development of English in Southeast Asia -- English in specific domains -- English as a lingua franca in ASEAN -- Language policy and language education -- Future of English and future challenges.
OCLC-licensed vendor bibliographic record.
Keywords: English language -- Dialects -- Southeast Asia; English language -- Study and teaching -- Southeast Asia; LANGUAGE ARTS & DISCIPLINES / Linguistics